The Response of Eggplant (Solanum melongena L) to Abiotic Stress and Organic Fertilizer: Respon Tanaman Terong (Solanum melongena L) Terhadap Cekaman Abiotik dan Pupuk Organik - Asiah Wati; Siti Mutmainah; I Gede Pasek Ista Darma (Universitas Widya Gama Mahakam, 2023)
ABSTRACT Efforts can be made to increase the production of eggplant plants in addition to land expansion and proper cultivation techniques. One effort to increase crop production is by adding nutrients and optimal irrigation. So it is necessary to study the response of eggplant (Solanum melongena L) to abiotic stresses and organic fertilizers with the aim of knowing the response to abiotic stresses, organic fertilizers and the interactions between abiotic stresses and organic fertilizers. The research method used a randomized block design (RBD) with abiotic stress treatment (C) with 4 levels, namely: c0 ; control without any stress, c1; 25% drought stress, c2 ; 50% drought stress and c3 ; 75% drought stress and the use of organic fertilizer (O) with levels namely: o0 ; without organic fertilizer, o1 ; organic fertilizer 200 g/poly bag, o2 ; organic fertilizer 400 g/poly bag and o3 ; organic fertilizer 600 g/polybag. The results of the research on drought stress treatment had a significant effect on the parameters of plant height, stem diameter, fruit length, fruit weight and number of fruit plants, the best results were at level c1, but had no significant effect on the initial age of flowering. Organic fertilizer treatment had an effect on stem diameter at 45 and 60 hst at o3 level but had no significant effect on plant height, plant diameter at 15 and 30 hst, early flowering, fruit length, fruit weight and number of fruit planted. There was no interaction in each treatment Keywords: food, climate. Sustainable ; 25% cekaman kekeringan, c2 ; 50% cekaman kekeringan dan c3 ; 75% cekaman kekeringan dan penggunaan pupuk organik (O) dengan taraf yaitu : o0 ; tanpa pupuk organik, o1 ; pupuk organik 200 g/polybag, o2 ; pupuk organik 400 g/polybag dan o3 ; pupuk organik 600 g/polybag. Hasil penelitian perlakuan cekaman kekeringan bepengaruh nyata pada parameter tinggi tanaman, diameter batang, panjang buah, berat buah pertanaman dan jumlah buah pertanaman hasil yang terbaik yaitu pada taraf c1 bernamun tidak berpengaruh nyata pada umur awal berbunga. Perlakuan pupuk organik berpengaruh pada diameter batang umur 45 hst dan 60 hst pada taraf o3 namun tidak berpengaruh nyata pada parameter tinggi tanaman, diameter tanaman umur 15 hst dan 30 hst, umur awal berbunga, panjang buah, berat buah pertanaman dan jumlah buah pertanaman. Tidak terdapat interaksi pada masing-masing perlakuan Kata kunci : pangan, iklim. berkelanjutan